Atitudes e Procedimentos de alunos frente à Leitura e Interpretação de textos nas aulas de Matemática - Salmazo, Rodrigo (2005)
The present work has as objective to study attitudes and procedures of students front to the reading and interpretation of texts in the mathematics classes e the purpose to contribute for the discuss and reflection of teachers of this relatively disciplines to the reading ability and writer of their students, of great importance for their pertaining to school, but also basic learning s for their performance in the social relations. It investigates as students of fifth and eighth grade of the basic education of a municipal school and third college students of a state school, both located in the city of Sao Paulo, react front to the reading of texts in the mathematics classes and search to identify to attitudes and procedures existing in this situation. Our study discloses that activities that involve reading, writing and interpretation of texts in the mathematics classes are outside in the mathematics classes and It leaves evident that in the activities that involve reading, writing and interpretation of texts in the mathematics classes a great dependence of the students in relation to the teacher is established. It still discloses that great part of the students have difficulties with the texts, as much in the reading, writing and interpretation and observed also great difficulty of concentration. The activities that involve reading, writing and interpretation of texts in the mathematics classes if show to the students as something laborious and desestimulante, but, where they weigh the difficulties that find in the activities that they involve reading, writing and interpretation of texts in the mathematics classes, the students recognize their importance. The study in it allows them to make recommendations in the direction of that it must have a way of double hand between reading, writing and interpretation of texts and the constitution to know mathematicians, in the mathematics classes and also that the studies on use and typology of texts would have to be object of inquiry in the area of mathematical education, searching to stimulate the development of different capacities of language and the use of different verbal sorts and writings.